The Relationship Between Interest and Emotional Intelligence to Learning Outcomes in Fitness Activities in Physical Education - FIDIANI AISYAH; DEFRI MULYANA; AANG ROHYANA; DICKY TRI JUNIAR (Universitas Pendidikan Indonesia, 2021)
Introduction: Intellectual intelligence (IQ) is needed in achieving learning achievement, but in some research studies, IQ is not the main factor in attaining learning achievement. Instead, there are other factors, namely emotional intelligence (EQ). Purpose: This study aims to find out information about the relationship between interest and emotional intelligence on learning outcomes. Methods: This research is descriptive quantitative with survey method. The population of this research is SMA KHZ Musthafa Sukamanah by taking a sample of class X using a proportional random sampling technique. From the secondary data that has been obtained in the form of the results of the assessment of fitness activity material by the teacher in which there is an assessment of cognitive, affective, and psychomotor then the author makes a questionnaire to be filled in by students. Results: Based on the interpretation table of the correlation value above, it can be seen that interest has a significant relationship with learning outcomes where the correlation value is 0.69 and is included in the moderate or sufficient category. Conclusions: Based on data processing using statistical tests, it turns out that empirically there is a relationship between interest and emotional intelligence on student learning outcomes.